The Effect of “Role Play” on Students’ Speaking Ability - Erlidawati Daulay; Linda Efrina Nasution; Ahmad Ripai Rangkuty (research, training and philanthropy institution Natural Aceh, 2023)
The objective of this research is to determine whether role-play significantly affects students' speaking ability at the tenth-grade students of SMA Negeri 1 Ulu Barumun.The population of this research is the tenth-grade students of SMA Negeri 1 Ulu Barumun, which is consisted of 205 students, and the sample was taken by cluster sampling that consists of 35 students. This research is carried out using the experimental method. Furthermore, the instrument used for collecting the data is by giving the test. After collecting the data, it was analyzed by using t.test.After analyzing the data, there is a significant effect of teaching speaking using role play teaching technique at the tenth-grade students of SMA Negeri 1 Ulu Barumun and categorized very well. It was found that the mean or the average of the student's score after the treatment was 83.11. Using statistical analysis, the researchers get to 42.05, where the value of t.table is 1.69. It means that the value of t observed is greater than that of the t table (to = 42.05 > t table = 1.69). It means that there is a significant effect of teaching by using role-play on students' speaking ability. The alternative hypothesis of this research is accepted. The value of the coefficient of determination is 0.86, which means role play affects the students' speaking ability by as much as 86 %.